Glass/sugar palm [Arenga pinnata (Wurmb. Merr.)] fibre- reinforced polypropylene hybrid composite automotive side door impact beam - Mukhtar, Isma'ila (2018)
Light-weight and high-performance materials are crucial in an automotive engineering. This is due to the numerous benefits such as low fuel consumption, cost savings and weight reduction. Traditionally, steel which is heavy and absorbed less energy when compared to composite is used as material for side door impact beam. Therefore, replacement of the steel beam is necessary to achieve weight reduction especially for hybrid and electric vehicle as well as improvement in energy absorption. This could be achieved with light-weight material such as natural fibre composites, though they are characterized with inferior mechanical properties. However, the inherent problems associated with natural fibre composites can be addressed through chemical treatments and hybridization. The sugar palm fibre (SPF) was selected based on its abundance especially in Southeast Asia and its proven performances. Therefore, this research describes the development and investigation of an automotive side door impact beam with glass/sugar palm (Arenga Pinnata) fibre reinforced polypropylene hybrid composite. In this study, the sugar palm fibre was treated with sodium hydroxide (NaOH) and sodium bicarbonate (NaHCO3). The properties of treated and untreated sugar palm fibre were evaluated through various characterization methods. Composite laminates of hybrid and non-hybrid glass/sugar palm fibre reinforced polypropylene were fabricated and characterized to study the effect of the treatment and hybridization. Consequently, hybrid and non-hybrid composite side door impact beams were fabricated and tested under three-point bending to determine their energy absorption and other performance parameters. The results showed that the treated SPF had an increase in crystallinity, thermal stability, and surface roughness when compared with the untreated fibre. Amongst the two different treatments, sugar palm fibre treated with alkaline had an initial decomposition temperature of 255.47 °C, while sodium bicarbonate treated and untreated fibre had 250.19 °C and 246.76 °C respectively. In both cases, the thermal stability of the fibre was improved. Also, as revealed by the X-Ray Diffraction (XRD) analysis, the cellulose content of SPF treated with alkaline and sodium bicarbonate increased by 22.6 % and 15.6 % respectively when compared with untreated fibre. These findings proved that treatment with the sodium bicarbonate had a significant effect on the physicochemical properties of sugar palm fibre and the chemical could be an alternative chemical for treating other cellulose fibres. Analysis of hybrid and a non-hybrid composite of SPF and glass fibre reinforced polypropylene composite showed a promising improvement in physiochemical properties of the composite. The tensile strength increased with both alkaline and sodium bicarbonate treatments for the hybrid and non-hybrid composites. The increase was more pronounced with alkaline treated SPF composite (L03) which displayed the highest value of 61.75 MPa. While that of sodium bicarbonate treated SPF composite (L04) recorded 58.76 MPa as against 53.01 MPa for the untreated SPF composite (L02). Likewise, an improvement was noticed for the flexural strength of the hybrid composite by 25.2% from 86.54 MPa to 108.34 MPa for alkaline treatment and by 13.9% from 86.54 MPa to 98.55 MPa for sodium bicarbonate treatment. Both the mechanical properties of the hybrid were significantly high compared to the non-hybrid composite. Furthermore, the results showed that the hybridization between sugar palm with glass fibre and/or chemical treatments gave a positive hybrid effect of the overall performance compared to the SPF/PP single system composite. In overall, the alkaline treatment yielded better performance in comparison with sodium bicarbonate treatment. Finally, the hybrid SPF/glass fibre reinforced PP composite beam (BMHC) exhibited the highest absorbed energy of 139.94 J, followed by glass fibre reinforced PP composite beam (BMC) with 104.47 J. This means that the hybrid composite had the capacity to absorb energy higher than the reference steel structure by 61.9 %. Furthermore, the hybrid composite beam allowed weight reduction up to 59.2 %. While the glass fibre reinforced PP composite beam recorded a reduced weight of 54.5 % when compared with a conventional steel beam. In conclusion, using sodium bicarbonate as the chemical treatment for sugar palm fibre can give the desired surface roughness with comparable thermal stability and tensile strength. Hybrid composite side door impact beam performed better in terms of weight reduction and energy absorption as compared to traditional steel beam.